Quiescin Sulfhydryl Oxidase 2 Overexpression Predicts Poor Prognosis and Tumor Progression in Patients With Colorectal Cancer: A Study Based on Data Mining and Clinical Verification - Jiang, Tao; Zheng, Li; Li, Xia; Liu, Jia; Song, Hu; Xu, Yixin; Dong, Chenhua; Liu, Lianyu; Wang, Hongyu; Wang, Shuai; Wang, Renhao; Song, Jun (Frontiers in Cell and Developmental Biology, 2021)
Background: Quiescin Sulfhydryl Oxidase 2 (QSOX2) is a member of the atypical thiol oxidase family and has been reported in several biological processes, but the expression and role of QSOX2 in colorectal cancer (CRC) remains elusive. Methods: The difference of QSOX2 expression, and it’ s relationship with clinicopathological features and prognosis in CRC was analyzed by bioinformatic analysis and validated by clinical CRC specimen cohort. The functional characterisation of QSOX2 in CRC and was investigated through a series of in vitro experiments while the potential signaling pathways were predicted by Gene Set Enrichment Analysis (GSEA). Results: QSOX2 is significantly upregulated in CRC tissues compared with adjacent non-tumor tissues (adjacent NTTs). The chi-square test indicated that high expression of QSOX2 was associated with Pathological stage (P=0.003) and Lymph node metastasis (P=0.003). Logistic regression analysis indicated that high QSOX2 expression was significantly associated with Pathological stage and Lymph node metastasis. Multivariate analysis suggested that high QSOX2 expression served as an independent significant predictor of poor overall survival (OS) (HR, 1.06; 95%CI, 1.00-1.13; P=0.033). The Kaplan-Meier curves showed that CRC patients with high QSOX2 expression exhibited a poor prognosis. Fisher’s exact test was used to examine the correlation of QSOX2 expression in cancer with clinicopathological characteristics while Kaplan–Meier survival analysis, log-rank test, univariate, and multivariate Cox regression models were used to examine whether QSOX2 expression was correlated with OS and disease-free cumulative survival (DFS) for CRC patients during the clinical validation phase. The data suggested that high QSOX2 expression was significant correlated with advanced clinicopathological parameters. In the meantime, CRC patients with a high level of QSOX2 protein expression trended toward correlation with worse OS and DFS compared with those with decreased QSOX2 expression. In vitro data showed that inhibition of QSOX2 suppresses cell proliferation, migration and invasion in CRC cells. In addition, GSEA showed that multiple signaling pathways were enriched in samples with high-QSOX2 expression phenotype. Conclusion: High QSOX2 expression is strongly associated with aggressive clinicopathological characteristics and poor oncological outcomes. QSOX2 might act as a potential prognostic biomarker and therapeutic target for CRC.